2017
DOI: 10.3892/etm.2017.4132
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide protects type II alveolar epithelial cells from hyperoxia-induced DNA damage and cell death

Abstract: Hyperoxia therapy for acute lung injury (ALI) may unexpectedly lead to reactive oxygen species (ROS) production and cause additional ALI. Calcitonin gene-related peptide (CGRP) is a 37 amino acid neuropeptide that regulates inflammasome activation. However, the role of CGRP in DNA damage during hyperoxia is unclear. Therefore, the aim of the present study was to investigate the effects of CGRP on DNA damage and the cell death of alveolar epithelial type II cells (AEC II) exposed to 60% oxygen. AEC II were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Oxygen is a double-edged sword since the preterm infants do not have an adequate amount of endogenous antioxidants to deal with oxidant injury, further predisposing them to the development of BPD or NEC [ 133 , 134 ]. The influences on cell growth brought by hyperoxia are either from the accumulation of inflammatory mediators or direct insult from reactive oxygen species [ 135 ]. These reactive species cause damage to not only cellular macromolecules [ 136 , 137 ], but also at the nuclear or mitochondrial DNA level.…”
Section: Recent Advances In Hyperoxia Exposure and Inflammatory Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen is a double-edged sword since the preterm infants do not have an adequate amount of endogenous antioxidants to deal with oxidant injury, further predisposing them to the development of BPD or NEC [ 133 , 134 ]. The influences on cell growth brought by hyperoxia are either from the accumulation of inflammatory mediators or direct insult from reactive oxygen species [ 135 ]. These reactive species cause damage to not only cellular macromolecules [ 136 , 137 ], but also at the nuclear or mitochondrial DNA level.…”
Section: Recent Advances In Hyperoxia Exposure and Inflammatory Pamentioning
confidence: 99%
“…Other cells in the lung are also affected by hyperoxia. The lung epithelium presented with markedly increased apoptotic cell numbers in the hyperoxia group and can be protected by Calcitonin gene-related peptide [ 135 ]. Fibroblasts help maintain alveolar and bronchial integrity, but following hyperoxia, significant morphological changes occur, with decreased proliferation and increased cell size, leading to a pro-fibrotic stage and resulting in abnormal repair in the lung [ 140 ].…”
Section: Recent Advances In Hyperoxia Exposure and Inflammatory Pamentioning
confidence: 99%
“…ATM alteration or insufficient expression is thought to be an important factor for cancer initiation and development. On the other hand, studies show that inhibition of ATM activity could be favorable for DNA‐damage based treatment including chemotherapy and radiotherapy . Moreover, higher ATM expression level in cancer cells is associated with drug resistance …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that CGRP has a protective role against hyperoxia-induced DNA damage and lung injury in type II alveolar epithelial (AEC II) cells and neonatal rats [ 10 , 11 ]. Another previous report demonstrated that CGRP is associated with the regulation of inflammatory cytokines [ 12 ].…”
Section: Introductionmentioning
confidence: 99%